2021
DOI: 10.1093/chromsci/bmab030
|View full text |Cite
|
Sign up to set email alerts
|

Quality-by-Design Approach for Chromatographic Analysis of Metformin, Empagliflozin and Linagliptin

Abstract: New analytical quality by design-oriented HPLC method with multiple response optimization (Derringer’s desirability function) was demonstrated for simultaneous analysis of three antidiabetic drugs (metformin hydrochloride/empagliflozin/linagliptin) in a fixed-dose combination. Central composite design was employed for systematic optimization of critical method parameters, namely, % organic phase (X1), aqueous phase pH (X2) and flow rate (X3) while resolution, capacity factor and theoretical plate number as cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The % of degradation was shown within the range of 12.9-2. 9 % at various stresses conditions and the % of degradation from a previous study was found within 7.76-0.13 % [29]. The proposed method was stability indicating as it is evidenced by clear separation of degradation peaks from analyte peaks in the chromatograms of forced degradation studies (fig.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The % of degradation was shown within the range of 12.9-2. 9 % at various stresses conditions and the % of degradation from a previous study was found within 7.76-0.13 % [29]. The proposed method was stability indicating as it is evidenced by clear separation of degradation peaks from analyte peaks in the chromatograms of forced degradation studies (fig.…”
Section: Discussionmentioning
confidence: 53%
“…about 10%-150% of the working concentration ranges of each drug, whereas in previously reported methods, the linearity of the calibration curve was ranged in 10%-100% [28][29][30] The very low measures of LOD and LOQ indicate better sensitivity of the proposed method for the analysis of metformin HCl, linagliptin, and empagliflozin [30][31]. The proposed method showed a remarkable outcome compared to a previous report with respect to low LOD and LOQ, particularly for metformin HCl [29]. The %RSD values of both method and intermediate precision were less than 2, which implies that the proposed method is precise.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Two analytical methods were reported to simultaneously determine the triple therapy MET, LIN and EMP using ultra high performance liquid chromatography (UPLC) [22] and thin-layer chromatography densitometric methods [23]. Another method was recently proposed by S. Gurrala et al ., where the study used the analytical Quality by Design (AQbD) paradigm and method operable design region (MODR) in optimization of a high performance liquid chromatography (HPLC) method for the simultaneous determination of the MET, LIN and EMP [24]. However, the article included many downsides that may have affected the validity and integrity of the applied AQbD and MODR procedures, e.g.…”
Section: Introductionmentioning
confidence: 99%